Activated carbon adsorbent
The activated carbon adsorbent with tailored pore characteristics and hardness effectively adsorbs low-molecular-weight compounds in the presence of high-molecular-weight compounds, addressing the limitations of existing adsorbents and enhancing therapeutic efficacy for kidney and liver diseases.
Patent Information
- Application Number
- JP2024552191
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-08-03
- Filing Date
- 2024-05-24
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2044-05-24
AI Technical Summary
Existing activated carbon adsorbents struggle to maintain high adsorption performance for low-molecular-weight compounds in the presence of both low- and high-molecular-weight compounds, such as in the human body environment where digestive enzymes and toxins coexist, leading to inadequate evaluation of adsorption phenomena.
The activated carbon adsorbent is designed with specific pore characteristics: a peak pore diameter of 0.52 to 0.70 nm, a pore volume of 0.45 to 0.55 cm³/g for sub-nanopores, a pore volume ratio of 3 to 50 for sub-nanopores to mesopores, and an average pore diameter of 1.7 to 5.0 nm, along with a hardness of 2.0 to 30.0 N, to ensure effective adsorption in the presence of both low- and high-molecular-weight compounds.
This design maintains high adsorption performance for low-molecular-weight compounds even in the presence of high-molecular-weight compounds, effectively adsorbing toxins while minimizing the adsorption of enzymes, making it suitable for therapeutic and preventive agents for kidney and liver diseases.
Smart Images

Figure 0007610765000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an activated carbon adsorbent having excellent adsorption performance for toxic substances. [Background technology]
[0002] Kidney and liver diseases are known to cause encephalopathy such as uremia and impaired consciousness due to the accumulation of toxic substances in the blood. Orally administered adsorbents that utilize the adsorption properties of activated carbon have been developed as treatments for mild kidney and liver diseases. This type of activated carbon adsorbent is required to selectively adsorb substances to be removed, such as uremic toxins, while minimizing the adsorption of useful substances, such as enzymes, in the body.
[0003] In general, enzymes are polymeric compounds with molecular weights of several tens of thousands, whereas toxins are low molecular weight compounds with molecular weights of several hundreds. Therefore, it is believed that in activated carbon adsorbents, a high degree of selective adsorption can be obtained by developing only the micropores that serve as adsorption sites for toxins. Thus, activated carbon adsorbents that aim to achieve both selective adsorption rate and indole adsorption rate by reducing the volume of mesopores to macropores (see, for example, Patent Document 1) and activated carbon adsorbents that aim to improve the adsorption performance of harmful substances in the presence of bile acids by reducing the pore volume of mesopores relative to the pore volume of micropores (see, for example, Patent Document 2) have been proposed.
[0004] In the case of the activated carbon adsorbent of Patent Document 1, when evaluating the selective adsorption, a method is generally used in which a plurality of single-component adsorption tests are carried out, such as by contacting the activated carbon with toxins and enzymes in separate systems to measure the adsorption rate of each substance, and the adsorption selectivity is evaluated based on the performance evaluation of each test. However, in the internal environment in which the activated carbon adsorbent is actually used, the adsorbent is considered to be affected by various macromolecular compounds such as digestive enzymes, such as inhibition of toxin adsorption, during the process of adsorbing toxins. Therefore, in the conventional performance evaluation based on the adsorption test of a single component, it is difficult to obtain an appropriate evaluation corresponding to the adsorption phenomenon in the internal environment in which digestive enzymes and the like are present.
[0005] Furthermore, for the activated carbon adsorbent of Patent Document 2, a method is adopted for evaluating the adsorption performance of toxic substances by a test in which indole is adsorbed in the presence of cholic acid, which is contained in large amounts in bile. However, since cholic acid, which coexists with indole, has an extremely small molecular weight compared to polymeric compounds such as digestive enzymes, it cannot be said to correspond to the internal environment in which digestive enzymes and the like are present, and it has been difficult to appropriately evaluate the adsorption phenomenon in the coexistence of polymeric compounds such as digestive enzymes.
[0006] The present inventors therefore conducted extensive research, assuming its use in an internal environment where digestive enzymes and the like are present, and have invented an activated carbon adsorbent that can maintain a high level of adsorption performance for low molecular weight compounds even in the coexistence of low molecular weight compounds that correspond to toxic substances and high molecular weight compounds that may inhibit toxin adsorption. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 6386571 [Patent Document 2] Patent No. 6306721 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been proposed in view of the above circumstances, and provides an activated carbon adsorbent that can maintain a high level of adsorption performance for low molecular weight compounds even in the coexistence of low molecular weight compounds and high molecular weight compounds. [Means for solving the problem]
[0009] That is, the first invention is a method for determining the peak of the pore diameter based on the pore volume (W p ) is 0.52 to 0.70 nm, and the pore volume (V SN ) is 0.45~0.55cm 3 / g, and the pore volume (V ME ) is 0.01~1.00cm 3 / g and an average pore diameter measured by the BET method is 1.7 to 5.0 nm.
[0010] The second invention is the first invention, wherein the pore volume (V ME ) to the pore volume of the sub-nanopores (V SN ) volume ratio (V SN / ME ) is 3 to 50.
[0011]
number
[0012] The third invention is the first or second invention, wherein the hardness (H D300 ) is 2.0 to 30.0N.
[0013] A fourth invention relates to the activated carbon adsorbent according to the first or second invention, which is an orally administered therapeutic or prophylactic agent for kidney disease or liver disease.
[0014] A fifth invention relates to the activated carbon adsorbent according to the third invention, which is an orally administered therapeutic or prophylactic agent for kidney disease or liver disease. Effect of the Invention
[0015] According to the activated carbon adsorbent of the first invention, the peak of the pore diameter based on the pore volume calculated by the GCMC method based on CO2 adsorption (W p ) is 0.52 to 0.70 nm, and the pore volume (V SN ) is 0.45~0.55cm3 / g, and the pore volume (V ME ) is 0.01~1.00cm 3 / g and the average pore diameter measured by the BET method is 1.7 to 5.0 nm, so that the adsorption performance for low molecular weight compounds can be maintained at a high level even in the coexistence of low molecular weight compounds and polymer compounds.
[0016] According to the activated carbon adsorbent of the second invention, in the first invention, the pore volume (V ME ) to the pore volume of the sub-nanopores (V SN ) volume ratio (V SN / ME ) is 3 to 50, the decrease in the adsorption performance for toxic substances can be suppressed.
[0017] According to the activated carbon adsorbent of the third invention, in the first or second invention, the hardness (H D300 ) is 2.0 to 30.0 N, the shape of the activated carbon particles is maintained, and the decrease in adsorption performance can be suppressed.
[0018] According to the activated carbon adsorbent of the fourth invention, in the first or second invention, the activated carbon adsorbent is an orally administered therapeutic or preventive agent for kidney disease or liver disease, and therefore has a high effect of selectively adsorbing causative substances of kidney disease or liver disease, and is suitable as a therapeutic or preventive agent.
[0019] According to the activated carbon adsorbent of the fifth invention, in the third invention, the activated carbon adsorbent is an orally administered therapeutic or preventive agent for kidney disease or liver disease, and therefore has a high effect of selectively adsorbing causative substances of kidney disease or liver disease, and is suitable as a therapeutic or preventive agent. [Brief description of the drawings]
[0020] [Figure 1] FIG. 2 is an image diagram of an adsorption phenomenon in an activated carbon adsorbent according to one embodiment of the present invention. [Diagram 2] FIG. 1 is an image diagram of an adsorption phenomenon in a conventional activated carbon adsorbent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The activated carbon adsorbent of the present invention has a pore diameter peak (W p ) and the pore volume of subnanopores with a pore diameter of 1.0 nm or less (V SN ) and the pore volume of pores with diameters of 3 to 50 nm (V ME ) and the average pore diameter.
[0022] The activated carbon adsorbent can be suitably used as a drug for oral administration, and is formed into a tablet shape using activated carbon as an adsorbent and additives as binders. The activated carbon adsorbent as a drug for oral administration is particularly used as a therapeutic or preventive agent for oral administration of kidney disease or liver disease. That is, since the activated carbon adsorbent has a high effect of selectively adsorbing causative substances of kidney disease or liver disease, the causative substances of disease or chronic symptoms are adsorbed and held in the pores on the surface by oral administration, and are excreted from the body, thereby suppressing the worsening of symptoms and improving the pathological condition. In addition, since the activated carbon adsorbent can reduce the concentration of causative substances of disease or chronic symptoms in the body by taking it in advance, it is considered to be effective as a preventive drug for suppressing the worsening of symptoms in cases of congenital or acquired metabolic abnormalities or those at risk of such disorders.
[0023] Examples of renal diseases include chronic renal failure, acute renal failure, chronic pyelonephritis, acute pyelonephritis, chronic nephritis, acute nephritic syndrome, acute progressive nephritic syndrome, chronic nephritic syndrome, nephrotic syndrome, nephrosclerosis, interstitial nephritis, tubulopathy, lipoid nephrosis, diabetic nephropathy, renal vascular hypertension, hypertension syndrome, as well as secondary renal diseases associated with these primary diseases and mild renal failure before dialysis, etc. Examples of liver diseases include fulminant hepatitis, chronic hepatitis, viral hepatitis, alcoholic hepatitis, hepatic fibrosis, liver cirrhosis, liver cancer, autoimmune hepatitis, drug-induced allergic liver disorder, primary biliary cirrhosis, tremor, encephalopathy, metabolic abnormality, functional abnormality, etc.
[0024] The raw material of the activated carbon adsorbent is preferably, for example, a resin carbonized product of a phenolic resin. The resin carbonized product of a phenolic resin can increase the ratio (volume ratio) of the sum of the mesopore volume to the sum of the micropore volume while increasing the activation and increasing the specific surface area, which makes it easier to improve the adsorption performance of toxic substances. Examples of the phenolic resin include known types such as novolac type, resol type, and composite phenolic resins of both types.
[0025] The activated carbon of the phenolic resin is preferably granular or spherical with an average particle size in the range of 20 to 1000 μm. If the average particle size of the activated carbon is too small, the activated carbon may become too dense when made into a tablet, resulting in poor disintegration. If the average particle size of the activated carbon is too large, the surface area where the activated carbon comes into contact with each other and bonds with each other due to the additive as a binder increases, which may weaken the binding force and reduce the hardness of the tablet.
[0026] The raw material for the activated carbon adsorbent can be cellulose instead of phenolic resin. When cellulose is used as the raw material, it is considered that by making the activated carbon with many macropores, it is possible to suppress the decrease in the adsorption performance derived from the activated carbon when it is made into a tablet form using an additive.
[0027] Pore diameter peak (W p) is the maximum value of the pore diameter based on the pore volume calculated by the GCMC method based on CO2 adsorption. 3 / g) is the pore volume of smaller micropores (diameter 1.4 nm or less) calculated by measuring the carbon dioxide adsorption isotherm at 298K and analyzing it by the GCMC method. The peak of the pore diameter based on the pore volume shifts in the direction of larger pore diameter as the activation of the activated carbon progresses. The preferred pore diameter peak is 0.52 to 0.70 nm. If the pore diameter peak is too small, toxic substances may not be adsorbed sufficiently. If the pore diameter peak is too large, it suggests that the activation is excessively advanced, and there is a risk of unnecessary adsorption of useful substances with large molecular weights such as in vivo enzymes.
[0028] The pore volume (V SN ) is a value calculated by measuring a carbon dioxide adsorption isotherm at 298K and analyzing it by the GCMC method. The pore volume of the subnanopore corresponds to an index of the adsorption performance of low molecular weight compounds, which are toxic substances. The pore volume of the subnanopore is preferably 0.45 to 0.55 cm 3 / g. If the pore volume of the subnanopores is too small, there is a risk that the adsorption performance of toxic substances will be insufficient. If the pore volume of the subnanopores exceeds a certain level, the subnanopores will join together to form larger micropores of 1 nm or more, so an upper limit is appropriately specified.
[0029] Pore volume (V ME) is a value calculated by the DH method based on N2 adsorption. This pore volume corresponds to the pore volume of mesopores with a pore diameter in the range of 3 to 50 nm, calculated by measuring a nitrogen adsorption isotherm at 77 K and analyzing it by the DH method (Dollimore-Heal method). The pore volume of pores with a diameter of 3 to 50 nm is the pore volume of mesopores corresponding to polymer compounds such as digestive enzymes, and corresponds to an index of the adsorption performance of polymer compounds. The pore volume of pores with a diameter of 3 to 50 nm is preferably 0.01 to 1.00 ml / g, more preferably 0.01 to 0.20 ml / g. If the pore volume of pores with a diameter of 3 to 50 nm is too small, the mesopores that serve as the diffusion paths of toxic substances to micropores may be blocked due to the influence of polymer compounds such as various enzymes present in the body, and the adsorption performance of toxic substances may become insufficient. If the volume of pores with diameters of 3 to 50 nm is too large, useful substances with large molecular weights, such as endogenous enzymes, may be unnecessarily adsorbed.
[0030] The average pore diameter is a value measured by the BET method. Specifically, assuming that the shape of the pores is cylindrical, the nitrogen adsorption isotherm at 77 K is measured, and the pore volume (mL / g) is calculated by analyzing the pore distribution by the DH method and the MP method. The specific surface area (m2) is calculated by measuring the nitrogen adsorption isotherm at 77 K and the BET method. 2 The average pore diameter is calculated from the following formula (ii) using the average pore diameter (m / g). The preferred average pore diameter is 1.7 to 5.0 nm, and more preferably 1.7 to 2.5 nm. If the average pore diameter is too small, there is a risk that the adsorption performance of toxic substances will decrease. If the average pore diameter is too large, there is a risk that useful substances with large molecular weights, such as endogenous enzymes, will be unnecessarily adsorbed.
[0031]
number
[0032] In the activated carbon adsorbent of the present invention, the pore volume (V ME ) versus the pore volume of the sub-nanopores (V SN ) volume ratio (V SN / ME) is preferably 3 to 50.
[0033]
number
[0034] This volume ratio (V SN / ME ) is the ratio of the pore volume of sub-nanopores intended for low molecular weight compounds to the pore volume of mesopores with a pore diameter in the range of 3 to 50 nm intended for high molecular weight compounds, and is 3 to 50, meaning that the pore volume intended for low molecular weight compounds is larger than the pore volume intended for high molecular weight compounds. This makes it possible to suppress the decrease in the adsorption performance for toxic substances when both compounds coexist. The volume ratio (V SN / ME If the volume ratio (V) is too small, the pore volume for low molecular weight compounds may be insufficient, resulting in a decrease in adsorption performance. SN / ME If the pore volume of the mesopores, which serve as diffusion paths for toxic substances, is insufficient, the adsorption of toxic substances is easily hindered, and the adsorption performance of toxic substances may decrease.
[0035] In addition, by satisfying the above-mentioned volume ratio, it is possible to suppress excessive adsorption of the polymer compound in the coexistence of the low molecular weight compound and the polymer compound. In particular, if the volume ratio is too small, the pore volume for the polymer compound becomes excessive, which is undesirable because there is a risk of the polymer compound being adsorbed more than necessary.
[0036] Furthermore, in the activated carbon adsorbent of the present invention, the hardness (H D300 ) is preferably 2.0 to 30.0 N. The average hardness is calculated as the average value of the crushing strength of any particle among activated carbon particles having a diameter of 150 to 500 μm, which is the particle size of activated carbon adsorbents for oral administration. In particular, in order to suppress the variation in hardness due to the particle size between samples, a linear function is derived from the crushing strength of approximately 20 arbitrary activated carbon particles, and the hardness (H D300It is desirable to calculate the hardness (H D300 If the hardness (H) is too low, the activated carbon particles may easily collapse, and the desired adsorption performance may not be obtained. D300 If the hardness is too high, it generally means that the activation is not sufficient and there are insufficient pores required for adsorption of toxic substances. By setting the hardness of activated carbon particles with a particle diameter of 300 μm to 2.0 to 30.0 N, the shape of the activated carbon particles can be maintained and the deterioration of adsorption performance can be suppressed.
[0037] As shown in the examples below, the activated carbon adsorbent of the present invention has a pore diameter peak of 0.52 to 0.70 nm, and a pore volume of sub-nanopores with a pore diameter of 1.0 nm or less of 0.45 to 0.55 cm. 3 / g, pore volume of pores with diameters of 3 to 50 nm is 0.01 to 1.0 cm 3 / g and the average pore diameter is 1.7 to 5.0 nm, it is possible to maintain a high level of adsorption performance for low molecular weight compounds even in the coexistence of low molecular weight compounds and high molecular weight compounds.
[0038] Therefore, the adsorption phenomenon of an activated carbon adsorbent specified by the pore diameter peak, the pore volume of sub-nanopores with a pore diameter of 1.0 nm or less, the pore volume of pores with a pore diameter of 3 to 50 nm, and the average pore diameter will be explained using the image diagrams in Figures 1 and 2. In the figures, reference numeral 10 denotes activated carbon particles, 20 denotes macropores, 30 denotes mesopores, 40 denotes micropores, 100 denotes activated carbon particles of a conventional activated carbon adsorbent, X and X1 denote low molecular weight compounds such as uremic toxins, and Y and Y1 denote high molecular weight compounds such as enzymes.
[0039] The activated carbon adsorbent of the present invention, in which the pore diameter peak, the pore volume of subnanopores with a pore diameter of 1.0 nm or less, the pore volume of pores with a pore diameter of 3 to 50 nm, and the average pore diameter are specified as described above, is assumed to have a pore structure in which a large number of mesopores 30 are formed within macropores 20 in activated carbon particles 10, and a large number of micropores 40 are further formed within each mesopore 30, as shown in Fig. 1. That is, the structure has a relatively large number of mesopores 30 corresponding to polymeric compounds as well as micropores 40 corresponding to low molecular weight compounds.
[0040] On the other hand, in conventional activated carbon adsorbents, the pore volume of the mesopores is reduced relative to the pore volume of the micropores, and therefore, as shown in Fig. 2, it is assumed that the activated carbon particles 100 have a pore structure in which there are few mesopores 30 within the macropores 20, and many micropores 40 are formed within each mesopore 30. In such activated carbon particles 100, the pore volume of the mesopores 30 is reduced relative to the pore volume of the micropores 40, and therefore, it is believed that a single-component adsorption test will show high adsorption performance for the low molecular weight compound X.
[0041] However, in an environment where low molecular weight compounds and high molecular weight compounds coexist, as shown in Fig. 2, when the high molecular weight compound Y1 is adsorbed into the mesopores 30, the entrance of the mesopores 30 having a large number of micropores 40 formed therein may be blocked by the high molecular weight compound Y1. Since the mesopores 30 having the micropores 40 formed therein correspond to a path (diffusion path) required for pore diffusion when the low molecular weight compound is adsorbed into the micropores, it is considered that the path of the low molecular weight compound X1 to the micropores 40 is blocked by the high molecular weight compound Y1 blocking the entrance of the mesopores 30. Furthermore, since there are few mesopores 30 in the macropores 20, it is considered that the rate at which the diffusion path of the low molecular weight compound X1 is blocked increases, resulting in a decrease in the adsorption performance of the low molecular weight compounds.
[0042] In contrast, in the activated carbon particles 10 of the activated carbon adsorbent of the present invention, a large number of mesopores 30 are formed within the macropores 20 in the activated carbon particles 10, and therefore, even if some of the mesopores 30 are blocked by the polymer compound Y1 as shown in Fig. 1, a large number of other open mesopores 30 are present, ensuring a path for the low molecular weight compound X1 to the micropores 40. Therefore, it is considered that the rate at which the diffusion path of the low molecular weight compound X1 is blocked is reduced, and a decrease in the adsorption performance for the low molecular weight compound is suppressed.
[0043] The activated carbon adsorbent of the present invention can be obtained by a known manufacturing method that includes a carbonization step of carbonizing an activated carbon raw material and an activation step of activating the carbonized product obtained by the carbonization step. In the carbonization step, the activated carbon raw material is placed in a firing furnace such as a cylindrical retort electric furnace, and the inside of the furnace is kept under an inert atmosphere such as nitrogen, argon, helium, etc., and carbonized at 300 to 1000°C, preferably 450 to 700°C, for 1 to 20 hours to obtain a carbonized product.
[0044] In the activation step, the carbonized material obtained in the carbonization step is placed in a known heating furnace or the like, and steam activation is performed at 750 to 1000°C, preferably 800 to 1000°C, and more preferably 850 to 950°C. The activation time is appropriate depending on the production scale, equipment, etc., and is preferably about 0.5 to 50 hours, for example. In addition to steam activation, gas activation such as carbon dioxide can also be used in the activation step. The activated activated carbon is washed with dilute hydrochloric acid, etc., and after washing with dilute hydrochloric acid, it is washed with water until the pH is about 5 to 7. The pH is a value measured in accordance with JIS K 1474 (2014).
[0045] After washing with dilute hydrochloric acid, heat treatment is performed in a mixed gas of oxygen and nitrogen and washing with water as necessary to remove impurities such as ash and hydrochloric acid remaining from the heat treatment. The oxygen concentration during the heat treatment is 0.1 to 21% by volume, the heating temperature is 150 to 1000°C, preferably 400 to 800°C, and the heating time is preferably about 15 minutes to 2 hours. In the activated carbon adsorbent, the amount of surface oxide is adjusted by undergoing each treatment, and the amount of surface oxide is increased through the heat treatment after acid washing.
[0046] The activated carbon adsorbent is not particularly limited in shape, but after activation treatment or after heat treatment following activation treatment, it is preferable to select granular or spherical activated carbon with an average particle size of 20 to 1000 μm, preferably 150 to 350 μm, by sieving. By selecting the particle size within the above range, the surface area of the activated carbon adsorbent can be appropriately secured. In addition, by adjusting and separating the particle size, the adsorption speed of the activated carbon adsorbent can be made constant and the adsorption capacity can be stabilized. That is, by making the particle size uniform, the adsorption performance in the digestive tract is stabilized, and the hardness of the particles is maintained, thereby suppressing further powdering in the digestive tract after oral administration (after ingestion). The preferred shape of the activated carbon adsorbent is spherical, but granular shapes are also included because variations in sphericity due to production are also acceptable.
[0047] The phenolic resin used as the raw material for activated carbon has an aromatic ring structure in the molecule, which increases the carbonization yield. Furthermore, activation produces activated carbon with a large surface area. The activated carbon after activation has a smaller pore size and a higher packing density than conventional activated carbon made from wood, coconut shells, petroleum pitch, etc. Therefore, it is suitable for adsorption of ionic organic compounds with relatively small molecular weights (molecular weights ranging from tens to hundreds) containing nitrogen, such as indoxyl sulfate, aminoisobutyric acid, tryptophan, which are representative of causative substances of uremia and their precursors. Furthermore, phenolic resin has less ash content such as nitrogen, phosphorus, sodium, magnesium, etc., and a higher ratio of carbon per unit mass than conventional activated carbon raw materials such as wood. Therefore, activated carbon with fewer impurities can be obtained. EXAMPLES
[0048] [Preparation of activated carbon adsorbent] The activated carbon raw material described below was used, placed in a cylindrical retort electric furnace, nitrogen was sealed inside, and then heat treatment was performed. Furthermore, steam was injected into the furnace for activation treatment, and activated carbon adsorbents of prototypes 1 to 16 were obtained.
[0049] [Prototype 1] As the activated carbon raw material, novolac resol composite spherical phenolic resin produced by a known manufacturing method was used. 1 kg of this phenolic resin was placed in a cylindrical retort electric furnace and nitrogen was sealed in, then the temperature was raised at 75°C / 1 hour, and the spherical phenolic resin in the furnace was carbonized by maintaining it at 600°C for 1 hour. The carbonized product was then heated to 900°C, steam was injected into the furnace, and the furnace was maintained at 900°C for 4 hours, and the steam was added to activate the carbon, to obtain the activated carbon adsorbent of Prototype Example 1.
[0050] [Prototype 2] Spherical phenolic resin (manufactured by Lignite Corporation) was used as the activated carbon raw material. 10 kg of this spherical phenolic resin was placed in a cylindrical retort electric furnace and nitrogen was sealed in, after which the temperature was raised at 50°C / hour and maintained at 600°C for 1 hour to carbonize the spherical phenolic resin in the furnace. The carbonized material was then heated to 900°C, steam was injected into the furnace, and the furnace was maintained at 900°C for 10 hours to add steam for activation, and an activated carbon adsorbent of prototype 2 was obtained.
[0051] [Prototype 3] Trial Example 3 is an activated carbon adsorbent obtained in accordance with Trial Example 2, except that the activation time was 27 hours.
[0052] [Prototype 4] Trial Example 4 is an activated carbon adsorbent obtained in accordance with Trial Example 2, except that the activation time was 33 hours.
[0053] [Prototype 5] Trial Example 5 is an activated carbon adsorbent obtained in accordance with Trial Example 2, except that the activation time was 37 hours.
[0054] [Prototype 6] Prototype 6 is a spherical adsorptive carbon (manufactured by Taewon Farm Company Limited, "Renamegin") that uses furan resin as the raw material for activated carbon.
[0055] [Prototype 7] Prototype example 7 is a spherical adsorptive carbon made from phenolic resin (manufactured by Nichi-Iko Pharmaceutical Co., Ltd., "Nichi-Iko").
[0056] [Prototype 8] Sample 8 is an activated carbon adsorbent obtained in accordance with Sample 2, except that the activation time was 40 hours.
[0057] [Prototype 9] Trial Example 9 is an activated carbon adsorbent obtained in accordance with Trial Example 2, except that the activation time was 52 hours.
[0058] [Prototype 10] Trial Example 10 is an activated carbon adsorbent obtained in accordance with Trial Example 2, except that the activation time was 56 hours.
[0059] [Prototype example 11] Trial Example 11 is an activated carbon adsorbent obtained in accordance with Trial Example 2, except that the activation time was 60 hours.
[0060] [Prototype 12] As the activated carbon raw material, spherical furan resin manufactured by Asahi Organic Chemicals Co., Ltd. was used. 500 g of this furan resin was placed in a cylindrical retort electric furnace and nitrogen was sealed in, after which the temperature was raised at 50°C / hour and the spherical furan resin in the furnace was carbonized by maintaining the temperature at 500°C for 1 hour. The carbonized product was then heated to 900°C, steam was injected into the furnace, and the temperature was maintained at 900°C for 5 hours, and the steam was added to activate the carbon, to obtain an activated carbon adsorbent of Prototype Example 12.
[0061] [Prototype 13] As the activated carbon raw material, the same novolak resol composite spherical phenolic resin as in Prototype 1 was used. 6 kg of this phenolic resin was placed in a cylindrical retort electric furnace and nitrogen was sealed in, and the temperature was appropriately maintained at 150 to 250 ° C to allow it to harden sufficiently. The temperature was then raised at 50 ° C / hour, and the spherical phenolic resin in the furnace was maintained at 600 ° C for 1 hour to carbonize it. The carbonized product was then heated to 850 ° C, steam was injected into the furnace, and the temperature was maintained at 850 ° C for 36 hours, and steam was added to activate the product, to obtain an activated carbon adsorbent of Prototype 13.
[0062] [Prototype 14] Trial Example 14 is an activated carbon adsorbent obtained in the same manner as Trial Example 1, except that the activated carbon raw material used was the same novolak resol composite spherical phenolic resin as in Trial Example 1, the heating rate was 50°C / hour, and the activation time was 6 hours.
[0063] [Prototype 15] As the activated carbon raw material, a flame-retardant treated spherical cellulose resin produced by a known manufacturing method was used. 400 g of this flame-retardant treated cellulose resin was placed in a cylindrical retort electric furnace, nitrogen was sealed in, and the temperature was raised at 50°C / hour and maintained at 250°C for 1 hour. The carbonized material was then heated to 900°C, steam was injected into the furnace, and the temperature was maintained at 900°C for 3 hours, and steam was added to activate the carbon, to obtain the activated carbon adsorbent of Prototype Example 15.
[0064] [Prototype 16] Trial Example 16 is an activated carbon adsorbent obtained in the same manner as Trial Example 1, except that the activated carbon raw material used was the same novolak resol composite spherical phenolic resin as in Trial Example 1, the heating rate was 50°C / hour, and the activation time was 8 hours.
[0065] [Measurement of activated carbon] For the activated carbon adsorbents of prototypes 1 to 16, the pore volume of the subnanopores, the pore volume of the ultramicropores, the pore diameter peak, the pore volume of all micropores, the pore volume of pores with diameters of 3 to 50 nm, the monolayer adsorption amount, the total specific surface area, the total pore volume, the average pore diameter, the average diameter of activated carbon particles, the average hardness of activated carbon particles, the hardness of particles with a diameter of 300 μm, and the volume ratio were each determined. The measurement results for each prototype are shown in Tables 1 to 3 below.
[0066] [Sub-nanopore pore volume] For the activated carbon adsorbents of Prototype Examples 1 to 16, the pore volume (cm) of the sub-nanopores (pore diameter less than 1 nm) 3The pore volume of the sub-nanopores was determined by measuring the carbon dioxide adsorption isotherm at 298K using a specific surface area / pore distribution measuring device (Microtrack-Bel Corporation's "BELSORP-miniII"), and analyzing the obtained carbon dioxide adsorption isotherm by the GCMC method, setting the activated carbon adsorbent to graphite carbon and the pore shape to a slit model.
[0067] [Ultramicropore volume] For the activated carbon adsorbents of Prototype Examples 1 to 16, the carbon dioxide adsorption isotherms obtained in the above measurements were analyzed by the GCMC method in the same manner, and the pore volumes (cm) of pores with diameters of less than 0.7 nm (ultramicropores) were calculated. 3 / g) were calculated respectively.
[0068] [Pore diameter peak] For the activated carbon adsorbents of Prototype Examples 1 to 16, the carbon dioxide adsorption isotherms obtained by the above measurements were similarly analyzed by the GCMC method to determine the peak of the pore diameter based on the pore volume at each pore diameter.
[0069] [Total micropore volume] For the activated carbon adsorbents of Samples 1 to 16, the nitrogen adsorption isotherm was measured at 77 K using an automatic specific surface area / pore distribution measuring device (Microtrack-Bell Corporation, "BELSORP-miniII"), and the pore distribution was analyzed by the MP method (Micropore method) to obtain the pore volume (cm) of 0.42 to 2 nm (total micropores). 3 / g) were calculated respectively.
[0070] [Pore volume with pore diameters of 3 to 50 nm] For the activated carbon adsorbents of Samples 1 to 16, the pore distribution was analyzed by the DH method for the nitrogen adsorption isotherms obtained in the above measurements, and the pore volume (cm) of 3 to 50 nm was calculated. 3 / g) were calculated respectively.
[0071] [Monolayer adsorption amount] For the activated carbon adsorbents of Prototype Examples 1 to 16, the monolayer adsorption amount (cm) was calculated by the BET method against the nitrogen adsorption isotherm obtained by the above measurement. 3 / g) were calculated respectively.
[0072] [Total specific surface area] For the activated carbon adsorbents of Samples 1 to 16, the total specific surface area (m 2 / g) was calculated (BET specific surface area).
[0073] [Total pore volume] For the activated carbon adsorbents of Prototype Examples 1 to 16, the total pore volume (cm) was calculated by the BET method against the nitrogen adsorption isotherm obtained by the above measurement. 3 / g) were calculated respectively.
[0074] [Average pore diameter] For the activated carbon adsorbents of Samples 1 to 16, the total specific surface area (m 2 The average pore diameter (nm) was calculated from the values of the molecular weight (g) and the total pore volume (mL / g) according to the above formula (ii).
[0075] [Average diameter of activated carbon particles] For the activated carbon adsorbents of Prototype Examples 1 to 16, 20 particles of activated carbon ranging from 150 to 500 μm were randomly selected, and the particle diameters were measured using a digital micrometer (manufactured by Shinwa Measurement Co., Ltd.). The average value was taken as the average diameter (μm).
[0076] [Average hardness of activated carbon particles] For the activated carbon adsorbents of prototypes 1 to 16, the diameters of the activated carbon particles were measured using the digital micrometer. The maximum crushing strength until the activated carbon particles were destroyed was measured using a digital force gauge (manufactured by Imada Co., Ltd., "ZTA-50N"), and the average value was taken as the average hardness (N).
[0077] [Hardness of particle diameter 300μm] For the activated carbon adsorbents of prototypes 1 to 16, the particle diameter and crushing strength data of 20 activated carbon particles measured by the above method were plotted, and a linear function was derived using a spreadsheet software. After confirming that the correlation coefficient of the graph excluding outliers was 0.7 or more, the hardness of a particle diameter of 300 μm was calculated from the linear function formula.
[0078] [Volume ratio] For the activated carbon adsorbents of Prototype Examples 1 to 16, the pore volumes (cm) of the sub-nanopores obtained by the above measurements were 3 / g) and the pore volume (cm) of mesopores with diameters in the range of 3 to 50 nm. 3 The volume ratio was calculated from the value of (1 / g) according to the above formula (i).
[0079] [Table 1]
[0080] [Table 2]
[0081] [Table 3]
[0082] [Adsorption performance test] For the activated carbon adsorbents of prototypes 1 to 16, a toxin adsorption test, coexistence adsorption test (1), and coexistence adsorption test (2) were conducted as tests of the adsorption performance of low molecular weight compounds in the coexistence of low molecular weight compounds and high molecular weight compounds.
[0083] [Toxin adsorption test] In the toxin adsorption test, three types of substances, "tryptophan", "indole", and "indole acetic acid", which are nitrogen-containing low molecular weight compounds that can cause uremia, were selected as toxic substances, and each substance was dissolved in a phosphate buffer solution of pH 7.4 to prepare a mixed solution of the three toxins at a concentration of 0.1 g / l. 0.1 g of each of the activated carbon adsorbents of prototypes 1 to 16, which had been previously dried by heating at 120 °C for 15 minutes or more in a static dryer, was added to the mixed solution of the three toxins, and the mixture was shaken in contact at a temperature of 37 °C for 3 hours. The filtrate obtained by filtration using a membrane filter was then subjected to gradient elution using a high performance liquid chromatograph (HPLC) (Agilent Technologies, Inc., "1260 Infinity II LC System") to determine the adsorption rate (%) from the difference in peak area before and after adsorption of each adsorbed substance (tryptophan, indole, indole acetic acid).
[0084] For gradient elution, an aqueous solution containing 0.05% trifluoroacetic acid was used as mobile phase A, and an ethanol solution containing 0.05% trifluoroacetic acid was used as mobile phase B. The separation column used was an "XBridge (registered trademark) Premier Protein BEH C4 300 Å 2.5 μm Column" (manufactured by Nihon Waters K.K.), the column heating temperature was set to 60° C., and the target substance was detected at a UV wavelength of 278 nm. Detailed gradient elution conditions are shown in Table 4.
[0085] [Table 4]
[0086] [Coexistence adsorption test (1)] In the co-adsorption test (1), three types of substances, "tryptophan," "indole," and "indole acetic acid," and one type of substance, "α-amylase," were selected as toxic substances and one type of enzyme (polymer compound), respectively, and a mixed solution of the three toxins and enzymes was prepared by dissolving each toxic substance at 0.1 g / l and α-amylase at 1 g / l in a phosphate buffer solution of pH 7.4. The adsorption rate (%) of each adsorbed substance (tryptophan, indole, indole acetic acid, α-amylase) was calculated using the same procedure as in the toxin adsorption test. Note that the concentration of α-amylase was set at 10 times that of the toxic substances because it has a higher molecular weight and the detected peak intensity is smaller.
[0087] [Coexistence adsorption test (2)] In the co-adsorption test (2), three types of substances, "tryptophan," "indole," and "indole acetic acid," were selected as toxic substances, and four types of substances, "α-amylase," "pepsin," "trypsin," and "lipase," were selected as enzymes. Each substance was dissolved in a phosphate buffer solution of pH 7.4 to prepare a mixed solution of the three toxins and four enzymes at a concentration of 0.1 g / l. The adsorption rate (%) of each adsorbed substance (tryptophan, indole, and indole acetic acid) was calculated using the same procedure as in the toxin adsorption test. Note that in the co-adsorption test (2), because it is technically difficult to separate the enzymes, the adsorption rate was calculated only for the toxic substances.
[0088] [Calculation of adsorption reduction rate] For each of the toxin adsorption test, coadsorption test (1), and coadsorption test (2), the average adsorption rate of the toxins in each adsorption test ([adsorption rate of the three toxins]÷3) was calculated from the calculated adsorption rates of the three toxins (tryptophan, indole, and indoleacetic acid). The average adsorption rate of the toxins in the toxin adsorption test was taken as the standard adsorption rate, and the average adsorption rate of the toxins in the coadsorption test (1) or coadsorption test (2) was taken as the coadsorption rate of each coadsorption test, and the adsorption reduction rate (%) was calculated using the following formula (iii). The adsorption reduction rate is an index showing the degree to which the adsorption rate of a low molecular weight compound decreases in the coexistence of a polymer compound compared to an environment in which the polymer compound does not coexist.
[0089]
number
[0090] [Evaluation of adsorption performance] The molecular weights of tryptophan, indoleacetic acid, and indole are small in the order of 204, 175, and 117, respectively. Indole is particularly easily adsorbed by activated carbon because of its high hydrophobicity, and is less susceptible to the effects of coexisting substances on the adsorption rate. Therefore, in each adsorption test, the adsorption rate of tryptophan, the adsorption rate of indoleacetic acid, and the average adsorption rate of toxins were evaluated as "good (○)" if they were 50% or more, and "bad (×)" if they were less than 50%, respectively. The adsorption rate of indole was evaluated as "good (○)" if they were 95% or more, and "bad (×)" if they were less than 95%. In addition, the adsorption rate and adsorption reduction rate of α-amylase were evaluated as "good (○)" if they were less than 30%, and "bad (×)" if they were 30% or more. The results and evaluations are shown in Tables 5 to 7.
[0091] [Table 5]
[0092] [Table 6]
[0093] [Table 7]
[0094] [Results and Discussion] For the activated carbon adsorbents of prototype examples 1 to 16, a toxin adsorption test was conducted in which toxic substances (low molecular weight compounds) and enzymes (high molecular weight compounds) did not coexist, a coexistence adsorption test (1) in which multiple toxic substances and one type of enzyme coexisted, and a coexistence adsorption test (2) in which multiple toxic substances and multiple enzymes coexisted.The changes in adsorption performance in the coexistence of low molecular weight compounds and high molecular weight compounds were examined from the measurement results shown in Tables 5 to 7.
[0095] In the toxin adsorption test, the adsorption performance for multiple toxic substances was measured in an environment where polymer compounds did not coexist. In prototype 1, the average adsorption rate of toxins exceeded the standard value, but the adsorption performance for tryptophan and indole acetic acid was insufficient. In addition, prototype 2 did not have sufficient toxin adsorption performance. On the other hand, prototypes 3 to 16 all showed good toxin adsorption performance.
[0096] In the coexistence adsorption test (1), the adsorption performance for multiple toxic substances was measured in an environment where multiple toxic substances coexisted with one type of enzyme. In the prototypes 1 to 7, although the adsorption rate of indole exceeded the standard value in some cases, the overall tendency was that the adsorption rate of each toxic substance was below the standard value, indicating that sufficient toxin adsorption performance could not be obtained in the coexistence of one type of polymer compound.
[0097] In addition, when focusing on the adsorption reduction rate, which is an index of the reduction in the adsorption rate of low molecular weight compounds in the coexistence of polymer compounds, among prototypes 1 to 7, prototypes 1 and 2, which showed a relatively low adsorption rate in the toxin adsorption test, showed a low adsorption reduction rate, while prototypes 3 to 7, which showed a good adsorption rate in the toxin adsorption test, showed a high adsorption reduction rate. This shows that, although prototypes 3 to 7 have good toxin adsorption performance, the toxin adsorption performance is significantly reduced in the coexistence of one polymer compound. In addition, prototypes 1 and 2 had a relatively low toxin adsorption performance, so the adsorption reduction rate was suppressed, but it was shown that the toxin adsorption performance in the coexistence was insufficient.
[0098] On the other hand, in the case of Prototypes 8 to 16, even in the presence of one polymer compound, the adsorption rate of each toxic substance and the average toxin were good, and the adsorption reduction rate was also low and good. Therefore, it was shown that Prototypes 8 to 16 have good toxin adsorption performance, and that the toxin adsorption performance is maintained at a high level even in the presence of one polymer compound.
[0099] In the coexistence adsorption test (2), the adsorption performance for multiple toxic substances was measured in an environment where multiple toxic substances and multiple enzymes coexisted. Prototypes 1 to 7 and 8 to 16 showed almost the same tendency as in the coexistence adsorption test (1). Therefore, it was shown that the toxin adsorption performance of Prototypes 1 to 7 decreased in the presence of multiple polymer compounds, while the toxin adsorption performance of Prototypes 8 to 16 was maintained at a high level even in the presence of multiple polymer compounds.
[0100] As described above, regardless of whether one or more polymer compounds are present, in the presence of polymer compounds, it was found that Prototypes 8 to 16 were able to maintain a high level of toxin adsorption performance, whereas the toxin adsorption performance decreased in Prototypes 1 to 7. Therefore, the differences in physical properties between Prototypes 8 to 16 and Prototypes 1 to 7 will be examined using Tables 1 to 3.
[0101] First, regarding the adsorption performance of toxic substances, prototypes 1 and 2 are compared with prototypes 3 to 16 based on the pore volume of subnanopores (pore diameter less than 1 nm) that are thought to correspond to the adsorption of toxic substances (low molecular weight compounds) and the pore volume of ultramicropores (pore diameter less than 0.7 nm). The pore volume of subnanopores was larger in prototypes 3 to 16, which had good adsorption performance, than in prototypes 1 and 2, which had insufficient adsorption performance for each toxic substance in the toxin adsorption test. On the other hand, no different tendency was observed in the pore volume of ultramicropores. This shows that the pore volume of subnanopores is effective as an index of the adsorption performance of toxic substances, and the measurement results of prototypes 3 to 16 show that the preferable condition is 0.45 to 0.55 cm. 3 / g.
[0102] Next, regarding the adsorption performance of toxic substances in the presence of coexistence, based on the pore diameter peak, pore volume of all micropores, pore volume of pore diameters of 3 to 50 nm, monolayer adsorption amount, total specific surface area, total pore volume, average pore diameter, average diameter of activated carbon particles, average hardness of activated carbon particles, hardness of particle diameter 300 μm, and volume ratio, Prototypes 3 to 7 and Prototypes 8 to 16 were compared. As a result, no different tendency was observed between Prototypes 3 to 7 and Prototypes 8 to 16 in the pore volume of all micropores, monolayer adsorption amount, total specific surface area, total pore volume, average diameter of activated carbon particles, average hardness of activated carbon particles, and hardness of particle diameter 300 μm.
[0103] On the other hand, the pore diameter peak, pore volume of pore diameters of 3 to 50 nm, average pore diameter, and volume ratio tended to differ between Prototypes 3 to 7 and Prototypes 8 to 16. The pore diameter peak corresponds to the pore diameter peak in the micropores, since the measurement range is the micropores by the GCMC method based on CO2 adsorption. Thus, when Prototypes 3 to 7 and Prototypes 8 to 16 are compared, the pore diameter peaks of Prototypes 8 to 16 were all larger than the pore diameter peaks of Prototypes 3 to 7.
[0104] The pore volume of pores with diameters of 3 to 50 nm corresponds to the range of pore diameters of 3 to 50 nm, which corresponds to the adsorption of enzymes (polymeric compounds), and can be used as an index of the adsorption performance of enzymes. Comparing Prototypes 3 to 7 with Prototypes 8 to 16, the pore volumes of pores with diameters of 3 to 50 nm in Prototypes 8 to 16 were all greater than the pore volumes of pores with diameters of 3 to 50 nm in Prototypes 3 to 7.
[0105] The average pore diameter can be used as one of the indices of the adsorption performance of an activated carbon adsorbent. Comparing Prototypes 3 to 7 with Prototypes 8 to 16, the average pore diameters of Prototypes 8 to 16 were generally larger than the average pore diameters of Prototypes 3 to 7.
[0106] Therefore, in activated carbon adsorbents, in addition to the pore volume of subnanopores, which is an indicator of toxin adsorption performance, the physical properties specified by the pore diameter peak, the pore volume of pores with diameters of 3 to 50 nm, and the average pore diameter can be said to be effective as indicators for maintaining a high level of adsorption performance for low molecular weight compounds (toxic substances) in the coexistence of low molecular weight compounds and high molecular weight compounds.
[0107] Therefore, considering the relationship between Prototype Examples 3 to 7 and Prototype Examples 8 to 16, the preferred conditions for the pore diameter peak, the pore volume with a pore diameter of 3 to 50 nm, and the average pore diameter are derived from the respective measurement results, and the pore diameter peak is about 0.52 to 0.70 nm, the pore volume with a pore diameter of 3 to 50 nm is 0.01 to 1.00 cm 3 / g and an average pore diameter of about 1.7 to 5.0 nm. In this case, an activated carbon adsorbent suitable for adsorbing toxins in the coexistence of toxic substances (low molecular weight compounds) and enzymes (high molecular weight compounds) is one with a subnanopore pore volume of 0.45 to 0.55 cm. 3 / g, it has excellent toxin adsorption performance, and the pore diameter peak is about 0.52 to 0.70 nm, and the pore volume of the pore diameter of 3 to 50 nm is 0.01 to 1.00 cm 3 / g and an average pore diameter of about 1.7 to 5.0 nm.
[0108] In addition, when comparing Prototype Examples 8 to 16, which are suitable for toxin adsorption in the presence of toxins, Prototype Example 16 had a higher adsorption rate of α-amylase in the coexistence adsorption test (1) than the other Prototype Examples 8 to 15. Considering the need to further improve the quality of the activated carbon adsorbent, a lower adsorption rate of enzymes such as α-amylase in the presence of toxins is preferable because it is less likely to cause side effects such as indigestion and loss of appetite. Thus, when the physical properties of Prototype Example 16 and Prototype Examples 8 to 15 were compared, the volume ratio of Prototype Example 16 was smaller than the other Prototype Examples 8 to 15.
[0109] The volume ratio is the ratio of the pore volume of subnanopores, which is an index of the adsorption performance of toxic substances, to the pore volume of pores with a diameter of 3 to 50 nm, which is an index of the adsorption performance of enzymes, and represents the balance between the subnanopores and the pores with a diameter of 3 to 50 nm in the activated carbon adsorbent. Since the volume ratio of prototype 16 is 0.54, it indicates that the pore volume of pores with a diameter of 3 to 50 nm is excessive compared to the pore volume of the subnanopores. Therefore, it is considered that prototype 16 adsorbed more α-amylase than necessary. Therefore, from the measurement results of prototypes 8 to 15, it is considered that the preferable condition for avoiding excessive adsorption of enzymes (polymer compounds) such as α-amylase is a volume ratio of about 3 to 50.
[0110] In addition, it is preferable that the activated carbon adsorbent has a predetermined hardness, assuming that it is formed into a tablet form or the like as a drug for oral administration. The preferred hardness of the activated carbon adsorbent is about 2.0 to 30.0 N for activated carbon particles with a particle diameter of 300 μm. Therefore, it was found that, among the activated carbon adsorbents of Prototypes 1 to 16, the activated carbon adsorbents of Prototypes 8 to 13 are good in terms of toxin adsorption performance in the presence of toxins, avoidance of excessive adsorption of enzymes, and hardness. [Industrial Applicability]
[0111] The activated carbon adsorbent of the present invention can maintain a high level of adsorption performance for low molecular weight compounds in the coexistence of low molecular weight compounds and high molecular weight compounds, and therefore can exhibit excellent toxin adsorption performance in an internal body environment in which low molecular weight toxic substances and high molecular weight enzymes coexist, making it a promising alternative to conventional activated carbon adsorbents. [Explanation of symbols]
[0112] 10 activated carbon particles 20 Macropores 30 Mesopores 40 Micropores 100 Activated carbon particles of conventional activated carbon adsorbent X,X1 Low molecular weight compound Y,Y1 polymer compound
Claims
1. CO 2 The peak of the pore diameter based on the pore volume calculated by the GCMC method based on adsorption (W p ) is 0.52 to 0.70 nm; The pore volume (V SN ) is 0.45 to 0.55 cm 3 / g, N 2 The pore volume (V) of pores with diameters of 3 to 50 nm calculated by the DH method based on adsorption ME ) is 0.01 to 1.00 cm 3 / g, The average pore diameter measured by the BET method is 1.7 to 5.0 nm. Activated carbon adsorbent characterized by:
2. The pore volume (V ME ) to the pore volume of the sub-nanopore (V SN ) volume ratio (V SN/ME 2. The activated carbon adsorbent according to claim 1, wherein the molecular weight of the activated carbon adsorbent is 3 to 50. [0010]
3. The hardness (H) of activated carbon particles with a particle diameter of 300 μm calculated from the average hardness of activated carbon particles with a diameter of 150 to 500 μm D300 3. The activated carbon adsorbent according to claim 1, wherein the concentration of the activated carbon adsorbent is 2.0 to 30.0 N.
4. 3. The activated carbon adsorbent according to claim 1, which is an orally administered therapeutic or prophylactic agent for kidney disease or liver disease.
5. 4. The activated carbon adsorbent according to claim 3, which is an orally administered therapeutic or prophylactic agent for kidney disease or liver disease.
Citation Information
Patent Citations
Orally administered pharmaceutical adsorbent with increased strength
JP2017507126A
Toxin separation instrument
JP2019150261A
Method for producing active carbon adsorbent
JP2020175383A
Tablet-type adsorbent for oral administration
JP2022038117A
Spherical activated carbon
KR101145131B1